Worker bees (Apis mellifera) deprived of pollen in the first week of adulthood exhibit signs of premature aging - Martelli, Felipe; Falcon, Tiago; Pinheiro, Daniel G. [UNESP]; Simoes, Zila L. P.; Nunes, Francis M. F. (Elsevier B.V., 2022)
Pollinator populations, including bees, are in rapid decline in many parts of the world, raising concerns over the future of ecosystems and food production. Among the factors involved in these declines, poor nutrition deserves attention. The diet consumed by adult worker honeybees (Apis mellifera) is crucial for their behavioral maturation, i.e., the progressive division of labor they perform, such as nurse bees initially and later in life as foragers. Poor pollen nutrition is known to reduce the workers' lifespan, but the underlying physiological and genetic mechanisms are not fully understood. Here we investigate how the lack of pollen in the diet of workers during their first week of adult life can affect age-related phenotypes. During the first seven days of adult life, newly emerged workers were fed either a pollen-deprived (PD) diet mimicking that of an older bee, or a control pollenrich (PR) diet, as typically consumed by young bees. The PD-fed bees showed alterations in their fat body transcriptome, such as a switch from a protein-lipid based metabolism to a carbohydrate-based metabolism, and a reduced expression of genes involved with immune response. The absence of pollen in the diet also led to an accumulation of oxidative stress markers in fat body tissue and alterations in the cuticular hydrocarbon profiles, which became similar to those of chronologically older bees. Together, our data indicate that the absence of pollen during first week of adulthood triggers the premature onset of an aging-related worker phenotype.
Keywords: Honey bees; Nutrition; Pollen; Oxidative stress; Cuticular hydrocarbons; Transcriptome; Aging